Muscle involvement in limb-girdle muscular dystrophy with GMPPB deficiency (LGMD2T). (December 2016) - Oestergaard, S.T.; Stojkovic, T.; Dahlqvist, J.R.; Bouchet-Seraphin, C.; Nectoux, J.; Leturcq, F.; Cossée, M.; Solé, G.; Thomsen, C.; Krag, T.O.; Vissing, J.
Abstract : Objective: In this study, muscle involvement assessed by MRI and levels of GMPPB and glycosylation of α-dystroglycan expression in muscle were examined in patients with limb-girdle muscular dystrophy (LGMD) type 2T. Methods: Six new patients with genetically verified mutations in GMPPB were studied. T1-weighted magnetic resonance images were obtained in 4 participants. Muscle strength and potential involvement of extramuscular organs were examined. Glycosylation of α-dystroglycan in muscle was studied, and GMPPB and α-dystroglycan expression was analyzed by Western blotting. Prevalence of LGMD2T was calculated from the total LGMD population in Denmark. GMPPB was sequenced in all unclassified cases. Results: Two patients carried 3 new mutations in GMPPB . The other 4 patients carried previously described pathogenic mutations in GMPPB . MRI showed that the paraspinal muscles were the most affected, followed by involvement of hamstrings. Our results showed a loss of glycosylation of α-dystroglycan as well as secondary loss of merosin expression on Western blotting. The prevalence of LGMD2T in the Danish cohort of patients with LGMD is 1.5%. Conclusions: The new findings of this study are (1) the consistent finding of a preferential affection of paraspinal and hamstring muscles in LGMD2T, (2) 3 new mutations in GMPPB, (3) variable loss of glycosylation tested with IIH6 and VIA4 antibodies, and (4) a prevalence of LGMD2T of 1.5% in a well-characterized Danish LGMD cohort.